2014
DOI: 10.4152/pea.201403213
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cathode Materials on Indirect Electrochemical Oxidation of Methyl Orange, Malachite Green and Methylene Blue

Abstract: The influence of cathode material on the electrochemical degradation of methyl orange (MO), methylene blue (MB) and malachite green (MG) dyes was investigated. The cathode materials used were platinum (Pt), copper (Cu), zinc (Zn) and aluminum (Al). The electrochemical activity of the selected dyes on the metal cathodes was examined by cyclic voltammetry (CV). The electrochemical treatment was carried out in both divided and undivided cells. The degradation process was monitored by UV-Visible spectroscopy and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Guenfoud et al [11] degraded 1 dm 3 of 20 mg dm À3 MGox by AO in a Diacell 500 flow plant equipped with a BDD/stainless steel (SS) cell and found 91% chemical oxygen demand (COD) reduction after 180 min in the presence of 0.1 mol dm À3 Na 2 SO 4 , at pH 3 and 32 mA cm À2 . Rao et al [48] reported a small effect of cathodes like Al, Cu, Pt and Zn on the decolorization and COD removal of Malachite Green by AO with a Pt anode, indicating its poor electroreduction ability. Better results were obtained by EF with Pt/graphite-felt tank reactors [18,19].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Guenfoud et al [11] degraded 1 dm 3 of 20 mg dm À3 MGox by AO in a Diacell 500 flow plant equipped with a BDD/stainless steel (SS) cell and found 91% chemical oxygen demand (COD) reduction after 180 min in the presence of 0.1 mol dm À3 Na 2 SO 4 , at pH 3 and 32 mA cm À2 . Rao et al [48] reported a small effect of cathodes like Al, Cu, Pt and Zn on the decolorization and COD removal of Malachite Green by AO with a Pt anode, indicating its poor electroreduction ability. Better results were obtained by EF with Pt/graphite-felt tank reactors [18,19].…”
Section: Introductionmentioning
confidence: 98%
“…The US Food and Drug Administration (FDA) has considered this dye as a priority chemical for carcinogenicity testing [43,44]. The destruction of Malachite Green with fast decolorization by TiO 2 photocatalysis [44], Fenton [45], photo-Fenton [45,46], zero-valent iron [47] and several EAOPs [11,18,19,48] has been described. Guenfoud et al [11] degraded 1 dm 3 of 20 mg dm À3 MGox by AO in a Diacell 500 flow plant equipped with a BDD/stainless steel (SS) cell and found 91% chemical oxygen demand (COD) reduction after 180 min in the presence of 0.1 mol dm À3 Na 2 SO 4 , at pH 3 and 32 mA cm À2 .…”
Section: Introductionmentioning
confidence: 99%
“…Counter Electrode : The cathode material is where the hydrogen evolution reaction occurs, completing the circuit and the redox reaction. It can affect the overall degradation reaction by electroreduction of the dissolved oxygen into H 2 O 2 , electroreduction of the organic pollutants or direct adsorption of these contaminants in porous cathodes …”
Section: Energy Balance Results For Different Configurationsmentioning
confidence: 99%
“…The conventional methods including electrooxidation [7], electro-Fenton [8], adsorption [9], ozone [10], photocatalytic [11], and reverse osmosis [12]. The electrooxidation method is an attractive technique used to treat textile effluents [13], while decontamination of the wastewater depends on the work electrodes in electrochemical reactors [14]. Copper, zinc, platinum, and aluminum were used as cathode material [14] to degrade MO and MB using an electrooxidation technique.…”
Section: Introductionmentioning
confidence: 99%